The Doctrine of God in the Theology of Heinrich Emil Brunner: A Theological-Biblical Assessment - Desmond Tutu Osei-Acheampong (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
Heinrich Emil Brunner’s doctrine of God has received a divergent view from biblical-theological scholars’ perspective. The doctrine of God has played a great significant and influential role throughout the era of Christian history, thus promoting the development and exploration of major theological doctrines in Christianity. The article therefore surveyed the canonical assessment of God’s doctrine in Brunner’s theology. It also sought to unlock Brunner’s hermeneutical method, contributors and opposers of his doctrine, and canonical approach in attaining salvific implications for contemporary Christians. The study employed a methodology of biblical-theological analysis to glean various literature materials. The findings revealed Brunner’s viewpoint that mankind can understand God through self-revelation. He opines that God possesses both communicable and uncommunicable tenets. Again, God is sovereign and supreme above all creatures in this world. In the light of this, God makes Himself known by His name. Thus, God as a Supreme Being, exhibits characteristic features of unknowable, innate, supernatural and He can be identified in His self-communication. God refers to Yahweh which depicts “I am that I am.” Thus, God is omnipotent, omnipresent, omniscient, immutable, honest, loving, and holy. Again, the doctrine of God unveils that God is infallible and hence He can assist human beings to live righteous life. The study concluded that the Lord is the creator, protector, and redeemer of humanity. The study unpacks that God’s salvific value could be realized through Jesus Christ. This study will be beneficial to biblical-theological historical students as it provides literature that will help advance and improve their studies.